Életformák
Dzsoni (Johnny) a young boy, building a small garden in the courtyard of a destitute condominium building, his father died, stepfather, program host Dr. Ilona Nagy, talking about the previously recorded documentary film, audience András Surányi, Dr. Ilona Nagy, Dr. János vizi